Alkaloids from the roots of Stemona javanica (Kunth) Engl. (Stemonaceae) and their anti-malarial, acetylcholinesterase inhibitory and cytotoxic activities - Ramli R.A.; Pudjiastuti P.; Tjahjandaric T.S.; Lie W.; Rattanajak R.; Kamchonwongapaisan S.; Pyne S.G. (Elsevier Ltd, 2024)
Indexed by WOS/ Scopus